(untitled) (SCIÉNDO INGENIUM, 2021)
The general objective of this research was to determine whether the decriminalization of sentimental abortion, typified in Article 120 of the Penal Code, will contribute to the decrease in the mortality rate of pregnant women as a result of rape. The methodology that was applied was quantitative, correlational level and non-experimental design, on a population composed of legal operators (lawyers, prosecutors and judges) of the Judicial District of Lima during 2020, finding the sample composed of 50 of them, being the type of probability sampling. Finally, the general conclusion was that the main effect that such decriminalization would have is to reduce the mortality associated with clandestine abortion.